Language-in-education planning in Tanzania: a sociolinguistic analysis - Tibategeza, Eustard Rutalemwa (University of the Free State, 2009)
The study presents a sociolinguistic analysis of the current language-in-education policy implementation in Tanzania. The current sociolinguistic thinking on bilingual education and language-in-education planning informs this evaluation. The analysis is presented against the background of the sociolinguistic principles of bilingual education as developed by García (1997). The challenges regarding implementation of bilingual education policy have been identified. The study indicates that there is no link between the envisioned ideals of the state to promote bilingual education and what obtains in the Education and Training Policy (1995), the document currently relied upon as far as language policy in the Tanzanian educational set-up is concerned. Chapter 1 provides the background of language-in-education planning and policy in Africa, where the advocacy for the use of African languages is high on the agenda. The obstacles, regarding the use of African languages alongside “imported” languages, are pointed out. The common obstacles range from the perseverance of the elite to maintain the status quo, the problem of language attitudes people have towards foreign languages such as English, French and Portuguese and more importantly lack of understanding of the concept of bilingual education and how it operates. Chapter 2 discusses bilingual education programmes with the view of monolingual education, weak and strong bilingual education. Sociolinguistic principles of bilingual education and theoretical considerations related to bilingualism also form part of this chapter. The theories explain some myths which people have regarding how the brain works when it comes to having two languages in education. In addition, language planning and policy concepts have been described to avoid the misconception held in some sociolinguistic literature that they are synonyms and aspects of the same activity. Language planning is seen as the activity that leads to the promulgation of a language policy while language policy is the body of ideas, laws, regulations, rules, procedures and practices intended to achieve the objectives of the policy. Chapter 3 discusses research methodology. The study is evaluative in nature and uses four research instruments, namely documentary reviews, interviews, observations and focus group discussions. Documentary review was meant to analyse the corpus of language-in-education policy documents created by relevant Tanzanian authorities to provide information on overt language policy and its implementation. The interviews were aimed at capturing information on views and perceptions of the education stakeholders regarding the concept of bilingual education and their understanding of the current policy and implementation. Observational method was specifically for supplementing the information gathered from interviews and facilitated cross-checking information in the policy documents. Similarly, focus group discussions provide further cross-checking and informs the development of the model for strong bilingual education. Chapter 4 provides a critical overview of language-in-education policy development in Tanzania from pre-colonial times to the present day. Language issues are discussed according to three different eras, namely pre-colonialism, during colonialism and post-independence. In all these eras, different languages, German, English, Kiswahili and ethnic languages were assigned different functions according to the motives the government in power had towards the languages. During colonial regime, German and English were preferable and they were regarded as languages of high status unlike Kiswahili and other ethnic languages. However, immediately after independence in 1961, the independent state put more efforts to promote Kiswahili. Chapter 5 focuses on data presentation and discussion. Challenges regarding the implementation of strong bilingual education policy in Tanzania are identified. They evolve around inadequate language-in-education policy design, inadequate comprehension of the concept of bilingual education and poor implementation strategies of the policy. Chapter 6 outlines the overview, overall conclusions and recommendation, where a viable and relevant model for implementing strong bilingual education in the Tanzanian sociolinguistic environment is proposed to guide the policy-makers tasked with language-in-education planning.
Thesis (Ph.D. (Linguistics))--University of the Free State, 2009
Keywords: Language and education -- Tanzania; Language planning -- Tanzania; Tanzania -- Languages; 50-50 dual language model; Medium of instruction; Principles of bilingual education; Bilingual education programmes; Biliteracy; Bilingualism; Language policy